The Impact of Payment and Respondents' Participation on Interviewers' Accuracy in Face-to-face Surveys: Investigations from a Field Experiment. Issue 4 (November 2018) - Menold, Natalja; Landrock, Uta; Winker, Peter; Pellner, Nathalie; Kemper, Christoph J.
In face-to-face interviews, accurate work by interviewers is crucial for ensuring high-quality survey data. In a field experiment, payment of interviewers, legitimation of falsification behavior, and respondents' willingness to participate were experimentally varied. The impact of these factors on interviewers' accuracy during fieldwork was investigated. Low accuracy was operationalized, for instance, as noncompliance with the instructions concerning contacting and recruitment. In addition, falsifications by interviewers were investigated. There were fewer deviations from prescribed routines, and interviewers' work was of higher quality if the interviewers were paid per hour and when respondents belonged to the cooperative group, compared to break-offs. We conclude that high task difficulty may lead to a decrease of interviewers' accuracy. Payment per hour seems to ensure higher-quality data and should be preferred.